Work-related musculoskeletal disorder: An occupational disorder of the goldsmiths in India - Ghosh Tirthankar; Das Banibrata; Gangopadhyay Somnath (Wolters Kluwer Medknow Publications, 2010)
Background: Gold ornament making industries are one of the widespread small-scale industries of India. These industries belong to the unorganized sector of the state. A large number of goldsmiths are working there for prolonged period in cross leg posture at semi-confined workstation. Objectives: The aim of this study is to identify Occupational Disorder of the Goldsmiths in India. Materials and Methods: In the spresent study, 120 male goldsmiths were randomly selected from the Davangere district of Karnataka. A detailed questionnaire study on discomfort feeling was done by the modified Nordic questionnaire, which considering the information about work nature, job stress and discomfort feeling. The existing workstations were assessed by the measurement of work areas. Analysis of body posture by rapid upper limb assessment was done to evaluate the work stress during their job. Results: From the analysis, it was revealed that MSDs were the major problem of the goldsmiths. The activities of the goldsmiths were also highly repetitive. Moreover, the questionnaire study revealed that most of the workers were affected by occupational disorder like pain at neck (80%), shoulder (20%), wrist (45%), and low back (75%) and also eye problem like irritation (30%) and burning sensation (70%). They also perform their job in hazardous postures. It was recorded that the workstations were poorly illuminated (19 Lux) in respect to precision work. Accidents like cut and burn occurred frequently due to the unsafe condition of the workstation. Conclusions: From the observation and analysis of the result it was concluded that health of the goldsmiths were highly affected improper body posture and workload. Twisting, bending, and over-reaching are the resultant of poorly designed workstation. These actions force them into a non-neutral position that increases the overall discomfort and pain at the lower back, neck, and shoulders. Moreover, lack of proper illumination at work site also exerts an additional adverse effect on the health of the goldsmiths.